Theory of laser-assisted autoionization by attosecond light pulses - Zhao, Z. X.; Lin, C. D. (My University, 2005)
We present a quantum theory of the decay of an autoionizing state created in the attosecond xuv (extreme ultraviolet) pump and laser probe measurements within the strong field approximation employing resonance parameters from Fano’s theory. From the electron spectra versus the pump-probe time delay, we show how the lifetimes of the resonances can be extracted directly from the time domain measurements.